PAKISTANI VENTURE CAPITALISTS’ INVESTMENT CRITERIA: A COMPARATIVE LOOK - Khoso Imamuddin (Asian Academy of Management Journal, 2009)
This paper has two objectives. First, it identifies investment criteria used by Pakistani venture capitalists (VCs) in the investment evaluation process. Second, it analyses how Pakistan VCs decision policies differ from their US and Indian counterparts. It is found that among Pakistani VCs, the factors related to the entrepreneur and management team are considered predominant and decisive in making investment decisions. Pakistani VCs rely heavily on a relationship-based approach in decision policies and may gradually move to a market-based approach once the economy's formal institutions attain stability. A relationship-based approach focusing on social networks can help substitute for formal institutions such as law, regulation and enforcement, which would facilitate the process of financial and non-financial transactions in the operation of venture capital markets in emerging economies. The differences I observed among US, Indian and Pakistani VCs decision policies regarding the use of investment evaluation criteria reflect the differences in institutional contexts. Moreover, I draw on agency theory to further view my survey results regarding the venture capital market in Pakistan. The results are in line with agency theory prescriptions that a relationship-based approach may be better suited to mitigate the agency problem, particularly adverse selection and moral hazard problems, by implementing the four prescriptions proposed by Ian and Peter (1994).